Differentiated Instruction for ASD Students in an EFL Class (NOBEL: Journal of Literature and Language Teaching, 2021)
his study aimed to investigate the implementation of Differentiated Instructions (DI) for Autism Spectrum Disorder (ASD) students in an EFL class and investigate the teachers’ views on the use of DI in an EFL class. This study employed a qualitative method and used an observation and interview checklist as the research instruments. Conducted in a private inclusive elementary school in Yogyakarta, Indonesia, this study involved three classes, i.e., grade 2, grade 3, and grade 6, and two English teachers who have experience teaching ASD students in an inclusive classroom setting. The observation and interview showed that DI was implemented in two ways, i.e., the English teachers designed different assessments for ASD students, and 2) the English teachers provided extra assistance for ASD students. The findings indicated that DI helped ASD students accomplish all in-class English assignments, and it helped ASD students follow the language of instructions in the English class. At the end of the article, implications and contributions for both in- and pre-service English teachers who teach ASD students in an inclusive class are offered.